2018
DOI: 10.1007/s00423-018-1710-1
|View full text |Cite
|
Sign up to set email alerts
|

Intensive perioperative rehabilitation improves surgical outcomes after pancreaticoduodenectomy

Abstract: Intensive perioperative rehabilitation might reduce postoperative pulmonary complications and shorten postoperative hospital stay after PD. Therefore, we suggest that perioperative rehabilitation should be included as part of enhanced recovery after surgery for patients undergoing PD, although further large-scale studies are necessary to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 41 publications
2
42
1
Order By: Relevance
“…A systematic review on prehabilitation in major abdominal surgery showed an overall reduction in postoperative complication rates with a greater effect of multimodal prehabilitation programs (26). Although prehabilitation has been shown to result in a significant reduction of pulmonary complications and length of hospital stay in patients undergoing a pancreatoduodenectomy, the benefit in improved clinical outcomes for esophagectomy patients has not yet been demonstrated (25,27,28).…”
Section: Improvement In Perioperative Carementioning
confidence: 99%
“…A systematic review on prehabilitation in major abdominal surgery showed an overall reduction in postoperative complication rates with a greater effect of multimodal prehabilitation programs (26). Although prehabilitation has been shown to result in a significant reduction of pulmonary complications and length of hospital stay in patients undergoing a pancreatoduodenectomy, the benefit in improved clinical outcomes for esophagectomy patients has not yet been demonstrated (25,27,28).…”
Section: Improvement In Perioperative Carementioning
confidence: 99%
“…Guidelines for ERAS protocol are based on these studies and applied in many hospitals worldwide [ 12 – 14 ]. Achieving the same goals, recent studies have shown the benefits of introducing other similar pathways, especially targeting perioperative rehabilitation and more precisely pre-habilitation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreaticoduodenectomy (PD) is one of the greatest challenges in gastrointestinal surgery, with mortality < 5% in high-volume centers, and even 50% of perioperative complications [1,2]. The anastomosis of the pancreatic stump is considered the most difficult phase of the surgery, crucial for postoperative healing.…”
Section: Introductionmentioning
confidence: 99%